MENDORONG PENSIUNAN UNTUK BERWIRAUSAHA: PELUANG DAN TANTANGAN UMKM DI INDONESIA - Rahman, Fadly (Taksasila Edukasi Insani, 2025)
Retirement is a time when someone starts a new life. There are many challenges faced by retirees in living their retirement life. One of them is the decreasing source of income that is usually not received every month. One solution is to encourage retirees to start becoming entrepreneurs. The opportunity to start with Micro, Small and Medium Enterprises (MSMEs) can be used as a solution to maintain retirement welfare.This paper aims to analyze the opportunities that can be utilized by retirees in starting a business, and the challenges faced when becoming entrepreneurs.This writing uses a qualitative approach by interviewing retirees who have become entrepreneurs and are running their businesses in the MSME sector. The results of this study indicate that becoming an MSME entrepreneur has an economic and social impact on retirees. Therefore, becoming an MSME entrepreneur can be a solution to maintain retirement welfare.To maximize the opportunities for retirees to start a business, support is needed from the company or workplace to conduct entrepreneurship training before leaving the company. Capital support from the government and assistance when starting a business.Keywords: Retirees, Entrepreneurs, MSMEs